Comprehensive review of PEO coatings on titanium alloys for biomedical implants - Cardoso, Giovana Collombaro [UNESP]; Grandini, Carlos Roberto [UNESP]; Rau, Julietta V. (Elsevier, 2024)
Titanium and its alloys are commonly utilized in the biomedical field for fabricating orthopedic and dental implants due to their favorable mechanical, chemical, and biological properties. However, titanium alloys exhibit limited or no bioactivity, necessitating the application of surface functionalization techniques to enhance their functional characteristics suitable for biomedical applications. Plasma Electrolytic Oxidation (PEO) treatment is a simple and versatile surface modification process for valve metals that can add superior osseointegration and bioactive properties to titanium and its alloys. Therefore, this review aims to summarize the mechanisms involved in obtaining porous coatings on the surface of titanium alloys using the PEO method, as well as to outline some of the physicochemical and biological properties of the resulting surfaces. The article discusses the mechanisms of action of bactericidal agents such as copper, silver, and zinc, commonly incorporated into PEO coatings. Finally, the study concludes by discussing remaining challenges and future perspectives that need to be addressed.
Keywords: Antimicrobial activity; Coatings properties; Micro-arc oxidation; Plasma electrolytic oxidation; Surface modification; Titanium alloys